Predictors of Life Satisfaction: The Role of Mindfulness and Locus of Control - Zadhasan, Zohreh (Journal of Personality and Psychosomatic Research (JPPR), 2024)
This study aimed to explore the extent to which locus of control and mindfulness predict life satisfaction among adults. Utilizing a cross-sectional design, 250 adults completed standardized measures assessing locus of control, mindfulness, and life satisfaction. Data were analyzed using multiple linear regression in SPSS Version 26 to determine the predictive power of locus of control and mindfulness on life satisfaction. Both locus of control and mindfulness emerged as significant predictors of life satisfaction, explaining 38% of the variance. Individuals with higher scores in mindfulness and a more internal locus of control reported greater life satisfaction. The findings underscore the importance of psychological constructs, such as locus of control and mindfulness, in enhancing life satisfaction. Interventions aimed at improving mindfulness and promoting an internal locus of control may be beneficial for boosting life satisfaction among adults.